THE IMPACT OF SUSTAINABLE TOURISM DEVELOPMENT ON THE FULFILLMENT OF DHARURIYYAT NEEDS THROUGH INCOME AS AN INTERVENING VARIABLE IN PULAU MERAH, BANYUWANGI - Hanima Khirda Luthfiana; Misbahul Munir; Siti Masrohatin (Adisam Publisher, 2025)
This study aims to examine the impact of sustainable tourism development on the fulfillment of dharuriyyat (essential) needs in Pulau Merah, Banyuwangi, by considering income as an intervening variable. The research is motivated by the increasing importance of tourism as a driver of regional economic growth, with the potential to elevate community welfare when implemented sustainably. Sustainable tourism is not only expected to support environmental and cultural preservation but also improve the economic conditions of local communities through enhanced income generation. Employing a quantitative explanatory research approach, data were collected through structured questionnaires from 130 respondents, comprising tourism actors and local residents. Path analysis was conducted using SPSS to assess direct and indirect effects among variables. The findings reveal that sustainable tourism development significantly and positively influences both income and the fulfillment of dharuriyyat needs. Additionally, income is found to have a strong effect on the fulfillment of these essential needs. However, income does not function as a mediating variable in the relationship between sustainable tourism development and dharuriyyat fulfillment. These results suggest that while sustainable tourism can directly enhance community welfare, the role of income as an intermediary is limited. The study underscores the importance of inclusive tourism development strategies, active community participation, and alignment with the maqashid al-shariah framework to ensure equitable benefits and sustainable welfare for local populations. Policy implications include the need for capacity-building programs, eco-friendly tourism incentives, and integrated planning that balances economic growth with the protection of social and environmental values.